Amyand's hernia: acute appendicitis and abscess in the inguinal canal. Issue 7 (10th July 2019) - Junttila, Anna; Mattila, Anne K
Abstract : Amyand's hernia is a rare entity where the appendix is trapped within inguinal canal. For even rarer are the cases where the appendix has perforated and caused an abscess into inguinal canal. Here we report a case where a male patient had Amyand's hernia, acute appendicitis and abscess which were treated by laparotomy. We present the diagnostic process and intraoperative finding leading to diagnosis of Amyand's hernia.